The Blind Men and the Elephant: Meta-Ethnography 30 Years On. (September 2019) - Brookfield, Samuel; Fitzgerald, Lisa; Selvey, Linda; Maher, Lisa
In the 30 years since its introduction, meta-ethnography has become a critical tool for synthesizing qualitative health research and providing a holistic understanding of complex health and social phenomena. Meta-ethnography has also been adapted to integrate a wider range of research methodologies, expanded to include a detailed taxonomy of research methods, and has led to the development of multiple other methods of synthesis. In this article, we describe the development of meta-ethnography, its unique research approaches, the innovations that have occurred since its inception, and potential future directions for the method. These include the need for consensus around the role of systematic database searches and critical appraisal, and a clearer path to action for clinicians interpreting qualitative research. Understanding and updating methods such as meta-ethnography will ensure that the exponentially developing field of qualitative research continues to have a meaningful and cumulative impact on complex issues of health and well-being.